Microtensile bond strength to sealer-contaminated dentin after using different cleaning protocols - Hai-Ling Zang; Sheng-Nan Ai; Yu-Hong Liang (Elsevier, 2022)
Background/purpose: Sealer residues on dentin may affect bonding to restorative materials. This study aimed to evaluate the bond strength to sealer-contaminated dentin after using different cleaning protocols. Materials and methods: Freshly extracted bovine incisors were prepared and exposed the buccal pulp chamber dentin, obtaining segments measuring 5 mm × 5 mm with a height of 3 mm. The segments were randomly distributed into 4 groups (n = 7) according to different protocols. Control group: no contamination was performed. In the three experimental groups, the segments were contaminated with epoxy resin-based sealer for 5 min, and different cleaning protocols were performed. Acetone group: acetone-saturated cotton pellets were used to wipe the sealer. Ultrasound group: ultrasonic ET-20D tip cleaning. Acetone combined with ultrasound group: cleaning with acetone-saturated cotton pellets and ultrasonic tip. All segments were bonded using a self-etch adhesive. Two samples in each group were scanned by swept-source optical coherence tomography (SS-OCT) to evaluate sealer residues. A microtensile test was performed on the remaining 5 samples, which were built up with composite resin. Results: Sealer residues were observed in 3 of 14 (21.4%) sections of acetone group by SS-OCT. Compared to the control, ultrasound alone or in combination with acetone preserved the bond strength (P > .05). The ultrasound group exhibited the highest bond strength (39.38 MPa), which differed from that of the acetone group, which provided the lowest bond strength (32.88 MPa) (P < .05). Conclusion: Cleaning epoxy resin-based sealer-contaminated dentin surfaces using ultrasound or combined with acetone could preserve the bond strength.